Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0020862.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cancer in Drosophila : The Next Generation

Abstract: Drosophila melanogaster , the vinegar fly, has been utilised as a genetic amenable model organism for more than 100 years. In recent years, its use in modelling human cancer has been greatly expanding. In this article, an update of the recent advances in Drosophila research towards understanding cancer development is provided. Genetic analysis in Drosophila has provided considerable insight into the mechanisms controlling tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…The development of malignant cancer requires the deregulation of many processes, including increased cell proliferation, reduced differentiation and apoptosis, increased invasion, and altered metabolism (reviewed in [ 157 ]). There are only a few tumour-causing genes that when individually knocked down or overexpressed in whole epithelial tissues or large domains, are capable of inducing all the hallmarks of cancer that can be modelled in Drosophila (reviewed in [ 3 , 11 , 15 , 158 ]). Many genes, when deregulated, can cause hyperplastic tumours, characterized by increased tissue growth that are still capable of differentiating, but only a few result in neoplastic tumours, in which the tissue overgrows and shows reduced differentiation and a loss of tissue architecture (reviewed in [ 159 ]).…”
Section: Cooperation Interactions Between Oncogenic or Tumour-suppmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of malignant cancer requires the deregulation of many processes, including increased cell proliferation, reduced differentiation and apoptosis, increased invasion, and altered metabolism (reviewed in [ 157 ]). There are only a few tumour-causing genes that when individually knocked down or overexpressed in whole epithelial tissues or large domains, are capable of inducing all the hallmarks of cancer that can be modelled in Drosophila (reviewed in [ 3 , 11 , 15 , 158 ]). Many genes, when deregulated, can cause hyperplastic tumours, characterized by increased tissue growth that are still capable of differentiating, but only a few result in neoplastic tumours, in which the tissue overgrows and shows reduced differentiation and a loss of tissue architecture (reviewed in [ 159 ]).…”
Section: Cooperation Interactions Between Oncogenic or Tumour-suppmentioning
confidence: 99%
“…Use of Drosophila as a model organism for cancer research was pioneered by genetic screens, conducted in the late 1900s, which identified many Drosophila tumour-causing mutations (reviewed in [ 16 , 17 ]). Many of these were novel tumour-suppressor genes or oncogenes, which were subsequently shown to also have tumourigenic properties in mammalian systems and to be involved in human cancer (reviewed in [ 8 , 9 , 11 , 18 , 19 ]).…”
Section: Introduction: Drosophila As a Model Fomentioning
confidence: 99%
“…Decades of fundamental research utilizing the vinegar fly, Drosophila melanogaster, have revealed many important genes and signalling networks that have subsequently proven to be important in human cancer (reviewed by [1][2][3][4]. Of particular interest for epithelial and neural cancers are the junctional neoplastic tumor suppressors, Lgl, Discs large (Dlg) and Scribbled (Scrib) (reviewed by 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular events that occur during cooperative tumorigenesis is critical in order to develop therapeutics to combat cancer. The model organism, Drosophila melanogaster (vinegar fly), has proven to be an excellent model for the discovery of new tumorigenic genes and the dissection of their roles in tumour progression, and has proven relevance to human cancer ( Brumby and Richardson, 2005 ; Cheng et al, 2013 ; Gonzalez, 2013 ; Rudrapatna et al, 2012 ; Stefanatos and Vidal, 2011 ).…”
Section: Introductionmentioning
confidence: 99%